Verdades e mentiras nas histórias de Alexandre: semiótica e letramento literário numa proposta didático-pedagógica - Sousa, Geórgia Karinne Soares Silva (2023)
This work aims to propose a didactic-pedagogical intervention for the development of literary literacy in the 9th grade of elementary school, associating the discursive configuration derived from the popular tale, from the perspective of a discursive theory, to reading and writing practices of students in the fanfiction genre. Thus, the research developed here sought to investigate how Discursive Semiotics can contribute to the process of interpreting these texts, enabling literary literacy. For this, three lines underlie the work: a legal and normative foundation, anchored mainly in the Law of Guidelines and Bases of Education, 9.394/96 and in the National Common Curricular Base (2018); a didactic-pedagogical foundation for the construction of an activity book based on the basic sequence elaborated by Rildo Cosson (2021) to promote literary literacy; and a discursive theory, the Discursive Semiotics, applied to the teaching of literature in the final years of elementary school, and brought in by the readings of Barros (1990, 1988) and Fiorin (2005). The methodological path traced goes from the reading of the short stories by Graciliano Ramos, the theoretical texts and the documents that support this research, to the survey of works inside and outside the PROFLETRAS program that focus on Discursive Semiotics, and on the literary text in question, to the elaboration of the activity notebook and its applicability in the classroom. Because it is a purposeful work, the activities suggested here, a result of this research, serve as support for Portuguese language teachers in elementary school.